Mitochondrial DNA Diversity in Commercial Lines of Laying-type Japanese Quail - Ryo Tadano (The Journal of Poultry Science, 2020)
The present study aims to investigate the maternal origin and genetic diversity of laying-type Japanese quail lines based on partial sequences (453 base pairs) of a mitochondrial DNA (mtDNA) control region. A total of 478 individuals from 12 lines were sequenced and six different haplotypes with eight variable sites were identified. All haplotypes, two of which were identical to previously reported sequences, were typical for the Japanese quail (Coturnix japonica) and were distinct from those of the common quail (Coturnix coturnix) in a phylogenetic analysis including other published haplotypes. One haplotype was distributed in the majority of individuals (84.9%, 406/478) across all lines. Within each line, 72.5–100% of individuals had this predominant haplotype. The second most common haplotype was detected in 12.8% (61/478) individuals. These two haplotypes accounted for 97.7% of all individuals. The remaining four haplotypes were distributed with a low frequency; these were observed in five, three, two, and one individuals across all lines, respectively. All lines showed a low degree of haplotype diversity ranging from 0.0000 to 0.4321. Genetic differentiation indexes (FST) were not significant in approximately 80% pairwise comparisons of lines. The results suggest limited maternal origin and low mtDNA diversity of laying-type quail lines and may reflect their breeding history where the present gene pool was rooted in a small number of founders.